Kinerja Usahatani dan Rantai Pasok Kelapa Sawit Rakyat Pola Mandiri Di Kabupaten Tulang Bawang Provinsi Lampung - Fitriani Fitriani; Fembriarti Prasmatiwi; R Hanung Ismono; Dyah Aring Hepiana Lestari (Politeknik Negeri Lampung., 2023)
Achieving the economic efficiency of the oil palm business is largely determined by the scale of the cultivation of the oil palm farms. This study aimed to analyze the performance of smallholder palm oil farming and its supply chains. This research used survey method. The research location was at the community oil palm plantation center in Tulang Bawang Regency, in Penawartama District and Gedung Aji Baru. The sample of oil palm farmers amounted to 74 respondents of farmers and the trader agents who involved in the supply chain. Analysis of farm performance used indicators of productivity, prices, farm cost efficiency, and income. Business scale can be divided into three classifications, as high, medium, and low business scale. Analysis of different tests of productivity, income and business scale using Least Squares Differences (LSD). Supply chains analysis used the S-C-P (Structure, Conduct, and Performance) model analysis. The results showed that the performance of independent smallholders of oil palm farming differed in their level of productivity and income on the scale of farming land, between small, medium and large landholders. The optimum of oil palm land makes a very significant difference in the level of palm oil farmers’ income received by smallholders on a large scale of land. While not significantly different between the scale of a narrow and medium scale. Oil palm fruit bunches (fresh fruit bunches FFB) supply chains involve marketing institutions namely lapak and agents as an extension of the palm oil mill. The flow of the independent farmer in FFB trading system involved many intermediaries as a market institution, that is, from the farmer-stall agent-the company raises the risk of low prices at the farm level. The assessment of FFB marketing performance illustrates the condition of price uncertainty with a reflection of the high FFB price range at the farm level. This puts the marketing performance of FFB not in favor of independent oil palm farmers.